SOME OBSERVATIONS ON THE HILSA FISHERY AT BUXAR (BIHAR, INDIA) IN THE YEARS 1952 TO 1954 - Jhingran, V G (Indian Journal of Fisheries, 2015)
Hilsa Uisha (Hamilton) forms an important commercial river fishe:-y in Bihar. Varma (1954) has described the Hilsa fishery in Bihar and has observed that the Arrah-Buxar area is the most prolific area in the whole of Bihar, wherefrom the largest catches of Hilsa are annually received. He has given Hilsa production figures for the year 1951. The present note gives the commercial landings of Hilsa at Buxar in the period May 1952 to December 1954, its season of abundance, the sizes which compose the commercial catches, the sex ratio, and the price of fish at source.